THE MAPPING OF ENGLISH LANGUAGE LEARNING PROBLEM (PBL)FOR PRIVATE HIGHER EDUCATION INSTITUTIONS IN BANDAR LAMPUNG - Rahayu, Mieke -; Septarina, Linda; Magdalena, Betty (Prosiding International conference on Information Technology and Business (ICITB), 2016)
This article discusses a mapping of problems of learning English encountered by students freshmen higher educations in Bandar Lampung. A set questionnaire which asked the learnersâ difficulties of learning English was distributed to 180 students fromÂ  higher education institutions: IBI Darmajaya, Universitas Bandar Lampung, STKIP PGRI, DCC,UniversitasSaburai and UniversitasParamadinaMandiri.UniversitasTulangBawang. From 180 students recruited for the study, 165students responded to the questionnaire. The questionnaire consists of 40 item Likert-scale questions asking students difficulties in comprehending andÂ  utilizing elements of pronunciaton, grammar, vocabular, functions, discourse and strategic in learning English.Â The results show that students encountered difficulties in pronunciations, vocabulary, function and strategic elements of English learning. Students did not encounter difficulties in discourse elements. This might be due to the fact that students got intensive trainings on discourse during their high school learning experiences.One of the implications of the study is a design of English course for higher education institutions in Bandar Lampung based the mapping of the problems encountered.Â Key words: mapping, Language Learning Problems, Higher Education institutions